(untitled) (New York, NY, 2007)
Effective Academic Writing presents the writing modes and rhetorical devices students need to succeed in an academic setting.
Keywords: English language,English language,English language,Academic writing; Rhetoric,Problems, exercises, etc.,Paragraphs,Problems, exercises, etc.,Textbooks for foreign speakers.,Problems, exercises, etc